Analisis Faktor Dominan yang Mempengaruhi Retensi Karyawan pada Perusahaan Manufaktur - Suci Indah Afiani; Andi Erna Mulyana (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2022)
This study aims to determine which factors are the most dominant of organizational commitment factors, career development, rewards, work environment, Work Life Balance that affect employee retention. The research method used is quantitative by using a questionnaire as a research data collection tool. This study uses a sampling technique that is random sampling and uses multiple linear regression analysis. The results showed that the factors of organizational commitment, career development, rewards, and work environment had an effect on employee retention. Meanwhile, the Work Life Balance factor has no effect on employee retention. Based on the results of the study, it was also found that among all the factors analyzed, the career development factor was the most dominant factor.